Optimalisasi Nilai Kearifan Lokal Rembug Pekon dalam Pengelolaan Taman Hutan Raya (TAHURA) Wan Abdurahman Propinsi Lampung sebagai Kawasan Hutan Konservasi Berbasis Masyarakat - Erlina B.; Bambang Hartono; Anggalana ANGGALANA; Melisa Safitri (KEADILAN PROGRESIF, 2018)
Optimizing the value of local wisdom Rembug Pekon in the management of the Great Forest Park (TAHURA) Wan Abdurahman as a community-based Conservation Forest area is viewed in a legal and social perspective, is an idea of the management of the Great Forest Park based on the social values of the community based on participatory principles, benefits , balanced and sustainable.The revitalization of Wan Abdurrahman Forest Park in Lampung Province of Indonesia as a communal forest park regarded in law and social perspective is a brainstorming of a communal nature preservation guided by the principle of participation, utilization, harmony, and sustainability. This idea is made for the improvement of Indonesia current policy which is considered for being ineffective due to the construction of “Top Down Planning” where the government is not only as the main brainstormer but also dominantly taking part in constructing the whole plan of the policy. Plainly, the government is playing a role not only as the law maker, but also the inspector. The community should have gotten a wide access to fight for their communal value. In short, our observation shown that the model of “Bottom Up Planning” is suit perfectly with all of the communities since it is seeking for the communal brainstorming in its whole policy and how easy for the people to deal only with their own social value. Each community must be actively taking place in making the policy construction of their social values while the government will only be the landlord. As a result, the whole communal values will be uplifted owing to the community habits as the part of the conservation legislations. This research is using the qualitative analysis used for assessing the policy related to the forest park utilization, initially projected the social norm of law or legislations. Undoubtedly, the interpretation is based on the theoritical interpretation, likewise generalized an ideal form of policy (ius constitutum). The advantages for stakeholders are to give an illustration academically in the form of policy analysis as well as to force the community participation and ensure that the whole policy and communal value collaboration will deliver so many risets related to the form of the public policy for both lecturer and also researchers expecting the implementation itself will be manifested in any kind of communal forest park area.